Vie chirurgiche d’accesso al gomito in traumatologia - Santolini, F.; Santolini, E.; Mangano, D.; Briano, S.; Sanguineti, F.; Felli, L.; Stella, M. (Lo Scalpello - Journal, 2018)
SURGICAL APPROACHES TO THE ELBOW IN TRAUMAThe elbow is a complex anatomical structure. The increasing amount of high energy trauma-related injuries hasrequired the development of several surgical approaches to allow for restoration of the anatomical joint surface and toobtain good clinical outcomes. In this article, we describe the main surgical approaches needed for the treatment ofsuch a complex pattern of traumatic lesions.